Outcomes in speech-language pathology - Golper, Lee Ann C.; Frattali, Carol (Thieme, 2013)
Based on the pioneering work of Carol C. Frattali,Outcomes in Speech-Language Pathology, Second Edition provides readers with a focused, comprehensive review of current policies, principles, and practices pertaining to outcome measurement in speech-language pathology with particular emphasis on healthcare. It is a unique text that covers outcomes in speech-language pathology practices within the context of contemporary issues across work settings that include clinical practice, applied clinical research, and graduate education.